Find the solution of 3^{4x} = 9^{(x-1)/2}.

First, recognise that 3^2 = 9. Recall the rule for multiplying indices, that (a^b)^c = a^{bc}. Then, substitute 3^2 in place of 9 to get 3^{4x} = (3^2)^{(x-1)/2}. Use the rule for multiplying indices, so that the equation is now 3^{4x} = 3^{x-1}. This implies 4x=x-1, and therefore 3x = -1, and finally, x = -1/3 is the solution.

Related Further Mathematics GCSE answers

All answers ▸

Given f(x)= 8 − x^2, solve f(3x) = -28


Work out the gradient of the curve y=x^3(x-3) at the point (3,17)


f(x) = 3x^3 – x^2 – 20x – 12 (a) Use the factor theorem to show that (3x + 2) is a factor of f(x). [2 marks] (b) Factorise f(x) fully. [3 marks]


f(x) = 2x^3+6x^2-18x+1. For which values of x is f(x) an increasing function?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences